Computation of Clinical Efficacy and Post- Thrombolytic Effects of Streptokinase in ST-Segment Elevated Myocardial Infarction Patients - Rajan, Asha K; Jeyamani S, Vedha Pal; R, Prakash; D, Prasanth; A, Praveen Kumar (Indian Journal of Pharmacy Practice)
Rationale: Atherosclerosis is a prominent underlying factor to Diabetes and Hypertension seen in 80% of patients leading to increased formation of thrombus thus blocking blood supply to myocardium. Fibrinolytics, such as streptokinase in the dose of 1,500,000 U in slow IV infusion has good activity for reperfusion. The study is aimed to evaluate the clinical efficacy and post-thrombolytic effects of streptokinase in STEMI patients. Materials and Methods: A prospective observational study of 100 patients of both sexes with STEMI was included based on inclusion and exclusion criteria. Demographic details of the patient, including ECG, Numerical Pain Rating Scale pain scale before and after fibrinolytic therapy were collected to record pain. Statistical significance was carried out with Students t-test, Chi- square test and SPSS software. Results: A marked change in ST segment elevation was observed with streptokinase therapy and decrease in coronary pain was measured when comparing before and after fibrinolytic therapy. At 90 min post thrombolytic therapy, 32 patients had pain relief (complete + partial), 11 patients had ST segment settlement (complete + partial) and 0 patients has T wave inversion. At the end of 48 hr of post thrombolytic therapy > 75% had pain relief, ≥ 50% patients had ST segment settlement and ≤ 10% patients had T wave inversion which was the least marker of reperfusion. Conclusion: Significant activity of streptokinase was obtained when used within 12 hr of resolution period. Chest pain, ST segment variations were the prominent markers for testing the efficacy of therapy.
Keywords: Acute coronary syndrome; Myocardial infarction; Streptokinase; Thrombolysis; ST segment elevation.